2011
DOI: 10.1007/s11947-011-0651-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Fortification on Physical and Sensory Quality of Gluten-Free Bread

Abstract: The scope of the present study was to investigate the effects of different iron compounds on the physical and sensory characteristics of gluten-free breads (GFBs) that were iron fortified (40 mg/kg solid compound) using different iron compounds. Differences among unfortified and fortified samples were observed in colour, crust firmness, and in the following sensory attributes: pore number, smell of 'moisture', metallic taste and stickiness. Elemental iron was more stable and thus adverse changes to product by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
3
17
0
1
Order By: Relevance
“…In this way, supplements of some of these micronutrients have been proposed to improve the quality of the gluten‐free diet (Caruso, Pallone, Stasi, Romeo, & Monteleone, ). However, there are very few studies on micronutrient fortification in GFBs, and all studies focus on iron (Kiskini et al., ; Kiskini, Kapsokefalou, Yanniotis, & Mandala, , ) and calcium fortification (Krupa‐Kozak, Altamirano‐Fortoul, Wronkowska, & Rosell, ; Krupa‐Kozak, Troszynska, Baczek, & Soral‐Smietana, ).…”
Section: Methodological Aspects Of Research On Commercially Availablementioning
confidence: 99%
“…In this way, supplements of some of these micronutrients have been proposed to improve the quality of the gluten‐free diet (Caruso, Pallone, Stasi, Romeo, & Monteleone, ). However, there are very few studies on micronutrient fortification in GFBs, and all studies focus on iron (Kiskini et al., ; Kiskini, Kapsokefalou, Yanniotis, & Mandala, , ) and calcium fortification (Krupa‐Kozak, Altamirano‐Fortoul, Wronkowska, & Rosell, ; Krupa‐Kozak, Troszynska, Baczek, & Soral‐Smietana, ).…”
Section: Methodological Aspects Of Research On Commercially Availablementioning
confidence: 99%
“…Over the world, the only proven treatment for coeliac disease is a strict and lifelong adherence to a gluten-free diet, which leads to the deficiency in nutrients components resulting none only from the intestinal abnormalities, but also from an insufficient supply of nutrients in gluten-free diet [13][14][15][16]. Patients showing nutritional deficiencies could require supplementation of their diets with vitamins, antioxidants, minerals, and proteins to correct deficiencies and restore nutrient reserves [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Electrolytic iron seemed to be more stable under heat treatment, and thus adverse changes to food by its addition were practically unobserved; however, it is usually poorly absorbed. The results from Kiskini and others (, ) help to understand the limitations of iron fortification in GFB. Curiously, Kiskini and others () observed that differences due to iron fortification were less pronounced in GFBs than in wheat‐containing breads.…”
Section: Micronutrientsmentioning
confidence: 99%
“…Based on the ferrous iron dialyzability, the predicted in vitro bioavailability of this compound was similar to or higher than other iron compounds tested. In a subsequent study, Kiskini and others () compared the effects of ferric pyrophosphate, ferric pyrophosphate with emulsifiers, sodium iron EDTA, microencapsulated ferrous sulfate, and elemental iron on the physical and sensory characteristics of iron‐fortified GFB (40 mg/kg solid compound). They observed that the addition of ferric pyrophosphate and NaFeEDTA caused undesirable changes in bread, like dark crust and crumb and a metallic taste.…”
Section: Micronutrientsmentioning
confidence: 99%